1979
DOI: 10.1111/j.1600-0560.1979.tb00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Malignant Spiegler Tumors with Brachydactyly and Racket‐Nails

Abstract: Multiple malignant Spiegler tumors were observed on the scalp of a 67-year-old female patient with brachydactyly and racket-nails affecting all fingers of both hands. The occurrence of similar clinical features in the family of the patient is suggestive of a hereditary disorder. The light and electron microscopical findings are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Although cylindromas liave been classified as apocrine tumors on the basis of light-and electron-microscope sttidies (55)(56)(57)(58)(59)(60), other ultrastructural findings and immunohistochemical data have suggested tbe occurrence of eccrine differentiation in such tumors (9,11,12,43,(61)(62)(63)(64)(65). As in previous studies (5,9,11,12,43,61), several of the markers used in the present study indicated a clear link with eccrine glands; however, none of the markers that we applied is capable of distinguishing between eccrine and apocrine differentiation, bl luminal cells, CK 6 and CK 19 were predominant, while CEA and EMA were also detected, thus confiriTting and extending previous findings (11,12); however, one study (5) has reported the absence of simple-epithelial CKs (PKK 1 antibody) in luminal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although cylindromas liave been classified as apocrine tumors on the basis of light-and electron-microscope sttidies (55)(56)(57)(58)(59)(60), other ultrastructural findings and immunohistochemical data have suggested tbe occurrence of eccrine differentiation in such tumors (9,11,12,43,(61)(62)(63)(64)(65). As in previous studies (5,9,11,12,43,61), several of the markers used in the present study indicated a clear link with eccrine glands; however, none of the markers that we applied is capable of distinguishing between eccrine and apocrine differentiation, bl luminal cells, CK 6 and CK 19 were predominant, while CEA and EMA were also detected, thus confiriTting and extending previous findings (11,12); however, one study (5) has reported the absence of simple-epithelial CKs (PKK 1 antibody) in luminal cells.…”
Section: Discussionmentioning
confidence: 99%
“…No follow-up information was given in 2 instances, Urbanski et al, have reviewed 9 previously reported cases with malignant transformation of cylindroma and added a case of their own with a large lesion of the scalp and underlying direct intracranial invasion. Most cases reported have been older individuals usually having multiple and longstanding lesions of the scalp (8)(9)(10)(11)(12)(13)(14)(15)(16), Multiple recurrences, lymph node involvement, and generalized metastasis have occurred in 7 cases (8),…”
Section: Commentsmentioning
confidence: 99%
“…They contain amorphous material that is composed of both acid and neutral mucopolysaccharides 7 . Instances of decapitation secretion by lumina cells have been described 9,10 …”
Section: Discussionmentioning
confidence: 99%